المصلحة المرسلة في المذهب الإباضي وتطبيقاتها المعاصرة : عقد التأمين وحقوق المؤلف نموذجا - المعولي, أحمد بن ناصر (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2024)
Keywords: Dynastie rustumide

Investigating the effective components on Fatimid relations with khariji religious other believers in the Islamic Maghreb - Mohammadi, Bahjat; Moradi Khalaj, Mohammad Mehdi (Historical Studies of the Islamic World, 2024)
AbstractThe formation of the Fatimid state in the Maghreb in 297 AH was the beginning of the Fatimid attempt to dominate the entire territory of the Maghreb as an all-encompassing state. This made the Fatimids' treatment of other believer groups in the Maghreb inevitable. other believers included Sunnis, Zaidi Shiites, and khariji religion who played important roles in the political, economic, and social spheres. Fatimid relations with these groups have been quite different based on religious and political circumstances. Based on a descriptive-analytical approach, the present study seeks to investigate the relationship between the Fatimids and khariji religion other believers of the Bani Rostam and Bani Madrar religions and the influence of religious, political and economic factors on these relations. Findings show that all three religious, political and economic components have played an important role in shaping these relationships. Although the religious and intellectual component has played a more prominent role and the intellectual and religious conflicts in the field of Imamate and Caliphate have been the infrastructure of Fatimid relations with this group of other believers; On the other hand, the effort to develop the land and form a powerful government, as well as access to the commercial interests of the region, has been one of the political and economic factors influencing the Fatimids' relations with khariji religious people.
Keywords: Dynastie rustumide

إمامة عبدالرحمن بن رستم للدولية الرستمية:, تحقيق في تاريخي البيعة والوفاة - بوشامة, أحمد (مجلة عصور, 2024)
Keywords: Dynastie rustumide

The Rustamid imamate: Building activities and military features as reported by Ibn al-Ṣaghīr - Schwartz, Werner (Between Morocco and Indonesia and beyond: Essays in honour of Irene Schneider, 2024)
Keywords: Dynastie rustumide

قراءة ونقد في قيم ومواقف المرأة الإباضية في عيون الشيخ محمد علي دَبُّوزْ من خلال مؤلفه تاريخ المغرب الكبير = Reading and Critique of The value system and Positions of the Ibadi Women in the eyes of Sheikh Muhammed Ali Dabouz as depicted in his book History of Greater Maghreb - بوعروة, بكير بن عيسى (مجلة العبر للدراسات التاريخية و الاثرية في شمال افريقيا, 2024)
الملخص باللغة العربية: الشيخ محمد علي الدَّبُّوزْ كاتب مؤرخ وأديب جزائري مميز، معاصر للاستعمار الفرنسي، له عدة مؤلفات مطبوعة، ومنها كتابه الشهير بتاريخ المغرب الكبير في ثلاثة أجزاء، ويتناول في جزئه الثاني تاريخ الدولة الرُّستميّة بشكل من التوسع، وهو كتاب هام إذ يتسم أسلوبه بمظهر أدبي واضح ونثر مميز وبديع، إضافة للمعارف التاريخية الغزيرة. من المعلوم أن المؤرخين لم يهتموا بالتاريخ الحضاري مثل اهتمامهم بالتاريخ السياسي، إلا أن الشيخ الدَّبُّوزْ تناول التاريخ الحضاري بشكل ظاهر من الإسهاب، وومما تميز به أنه كتب بشكل مطول عن المرأة الإباضية ودورها في قيام الدولة الرُّستميّة بأسلوب أدبي متين ، وقد بدأ سرد تاريخه منطلقا من أرض المشرق وصولا إلى أرض المغرب الإسلامي، وهو أحيانا يغرق في بعض التفاصيل الدقيقة، ويبدو مركزا بشكل واضح على القيم الثورية والحماس الوقاد والاغتراف من المعارف والعلوم؛ من أجل قيام الدولة المنشودة ذات الجذور الرصينة المبنية على الخلافة الراشدة كما يعتقد، وهو في شق آخر يتناول الجانب الإثني ودوره في الثورة، إذ الثورة من سمات البربر منذ الأزل كما يقول ويؤكد عليه، وحتى لا يفهم كلامه خطأ فإنه يشير بوضوح إلى بغضه للتعصب والخلاف، وإلى ذلك فهو يبغض بشكل واضح مظاهر النساء التي رآهن زمن المستعمر الفرنسي، إذ يقارن بين الضدين، ويؤسس ويدعو لمنظومة القيم ومن ضمنها قيم الدولة الرُّستميّة أنموذجا قيما. يعتبر الشيخ الدَّبُّوزْ ناقلا لمعارفه من المصادر الإباضية التي يشير لها بوضوح، وقد نقل عن مصادر ومراجع أخرى أشار لها في النص، إلا أنه تفرد أنه مرجع قيم عام جامع مانع لمختلف أخبار وسير وتاريخ النسوة الإباضيات بشكل موسع، وبالتأكيد هناك دراسات قيمة مذكورة في البحث، إلا أنها مختصرة ومركزة مقارنة بما كتبه الشيخ الدَّبُّوزْ الأديب المؤرخ الأريب. Abstract: Sheikh Muhammad Ali Dabouz is a distinguished writer, historian and writer, contemporary with the French colonialism. He has several published books, including his famous book, The History of the Great Maghreb in three parts. In its second part, it deals with the history of the Rustamid state. abundant historical. It is well known that historians did not care about cultural history as much as they care about political history, but Sheikh Dabouz dealt with cultural history in a way that appears, but rather he wrote in his solid and lengthy style about Ibadi women and their role in the establishment of the Rustamid state, starting from the land of the East to the land of Morocco, which is drowning in Some subtle details, and we see it clearly focused on revolutionary values enthusiasm and transfer of knowledge and science; For the sake of the establishment of a state with solid roots based on the rightly guided caliphate, and in another part that deals with the ethnic aspect and its role in the revolution, as the revolution is one of the characteristics of the Berbers since time immemorial, as he says and affirms it, and in order not to misunderstand his words, he clearly indicates his hatred of intolerance and disagreement, and to that he He clearly hates the appearances of women that he saw during the time of the French colonizer, as he compares the two opposites, and establishes and calls for a system of values, including the values of the Rustamid state as a valuable model. Sheikh Dabouz is considered a transmitter of his knowledge from the Ibadi sources that he refers to clearly, and he quoted other sources and references that he referred to in the text, as he did not depend on the marginalization that is currently in force, but he is unique as a comprehensive general values reference that prevents the various news of Ibadi women extensively, and certainly There are valuable studies mentioned in the research, but they are brief and focused compared to what Sheikh Dabouz wrote.
Keywords: Dynastie rustumide

The issue of Imamate and succession and its influence in creating religious conflicts of Khawarij Ābāḍi Bani Rostam - Ezati, Mehdi (Motaleat-e-Taghribi Mazaheb-e-Eslami, 2024)
Following the preaching activities of the Ābāḍiyya jurists in the first half of the second century of the Hijri, the Ābāḍiyya religion was able to attract many followers among the Berber tribes of North Africa. Finally, in the middle of the 2nd century, Ibn Rostam established the Ābāḍiya government in the eastern regions of the Middle Maghreb. According to the principles of the Ābāḍian Bani-Rostam religion, the selection of the imam was based on the council of jurists and tribal sheikhs and the imam could be from any race or tribe. Based on this, Abdurrahman bin Rostam, who was non-Arab and Iranian, and of course she had the conditions for Imamate, was elected as Imam and leader of Abadi religions by the council of sheikhs and jurists. Although apparently Abd al-Wahhab bin Abd al-Rahman also achieved the Imamate of the Ābāḍians through the council, but according to some Abadian jurists, this choice was also a hereditary method and the Imamate was somehow passed from father to son. The method of hereditary Imamate continued in the rule of Bani Rostam until the end of their dynasty, and this issue caused tension and disagreement between some of the Ābāḍi jurists and the rulers of Bani Rostam. This essay will investigate this issue and the challenges faced by Bani-Rostam imams regarding the subject of Imamate with a descriptive-analytical method. The findings showed that due to the main orientation of Bani Rostam rulers in inheriting the government which was influenced by Iranian thought, they faced widespread oppositions and uprisings during their rule.
Keywords: Dynastie rustumide

L'origine persane de la dynastie rustumide chez les chroniqueurs ibadites maghrébins (IXe-XVIe) - Bahmani, Salah (Généalogies arabes des dynasties non arabes: Une quête de légitimité inattendue en Islam médiéval et moderne (IXe-XVIIIe s.) ?, 2024)
Keywords: Dynastie rustumide

As-Samḥ oder al-Masīḥ? Zur Frage einer christlichen Gemeinde in Tāhart im 3./9. Jahrhundert - Schwartz, Werner (Teachers and Students, Reflections on Learning in Near and Middle Eastern Cultures: Collected Studies in Honour of Sebastian Günther, 2024)
Keywords: Dynastie rustumide